Correlation Neglect in Belief Formation. (22nd December 2017) - Enke, Benjamin; Zimmermann, Florian
Abstract: Many information structures generate correlated rather than mutually independent signals, the news media being a prime example. This article provides experimental evidence that many people neglect the resulting double-counting problem in the updating process. In consequence, beliefs are too sensitive to the ubiquitous "telling and re-telling of stories" and exhibit excessive swings. We identify substantial and systematic heterogeneity in the presence of the bias and investigate the underlying mechanisms. The evidence points to the paramount importance of complexity in combination with people's problems in identifying and thinking through the correlation. Even though most participants in principle have the computational skills that are necessary to develop rational beliefs, many approach the problem in a wrong way when the environment is moderately complex. Thus, experimentally nudging people's focus towards the correlation and the underlying independent signals has large effects on beliefs.